Conductive Metal–Organic Frameworks: Design, Synthesis, and Applications. Issue 10 (16th July 2020) - Meng, Haibing; Han, Ying; Zhou, Chenhui; Jiang, Qinyuan; Shi, Xiaofei; Zhan, Chenhao; Zhang, Rufan
Abstract: Metal–organic frameworks (MOFs) have aroused worldwide interest over the last two decades due to their various excellent properties, such as porosity, modifiability, stability, etc. Based on these unique features, they have been widely exploited for applications from electrocatalysis to electrochemical devices. However, most MOFs are inherently insulated due to the lack of free charge carriers and low‐energy barriers for charge transfer, which largely restricts their further electrochemical applications. By imparting MOFs with electrical conductivity, their electrochemical process and catalysis efficiency can be effectively improved. Similarly, their applications in sensors, secondary batteries, electrochemical devices, etc., can be well developed. Over the past few years, many conductive MOFs have been constructed by formatting composite, postsynthesized modification, introducing guest molecules, etc. Meanwhile, their electrochemical applications depending on their good conductivity have been investigated detailedly. However, it remains a challenge to endow most MOFs with high conductivity due to the tedious synthesis process and weak charge transfer properties of MOFs. In this review, the latest designs and synthesis strategies of conductive MOFs as well as their conductive mechanisms are summarized. The direct/postsynthesis methods are mainly focused for constructing conductive MOFs. In addition, their applications in sensors, energy conversion, electronics, etc., are also introduced. Abstract : In this review, the up‐to‐date strategies for designing and synthesizing conductive MOFs and their conductive mechanisms are introduced and discussed. Besides, the electrochemical applications of MOFs based on their high conductivities are summarized. Furthermore, some conclusions are received about the constructions and applications of conductive MOFs as well as put forward some outlooks for the development of conductive MOFs.